A review of the applied behavioral neuroscience research used to develop the QCore™ tinnitus therapy platform - Grant D. Searchfield (Frontiers in Audiology and Otology, 2026)
Background Tinnitus is a heterogeneous disorder of hearing with a complex biopsychosocial basis. This paper reviews the research used in the development of the QCore™ Tinnitus Therapy Platform. Methods A narrative review based on a non-systematic literature search. The review describes the research underpinning the development of 3 QCore™ therapy modes (Relief, Relax, and Retrain) and compares them with major tinnitus guidelines. Results Based on an ecological model of tinnitus and adaptation-level theory, the therapy's goal is to reduce the perceived magnitude of tinnitus by desensitizing a core tinnitus network. Evidence used in developing the hypothesis is reported from multiple behavioral and physiological studies. Discussion The research supports the notion that therapy modes have different behavioral and physiological effects, consistent with changes in tinnitus audibility, annoyance, and attention. Much of the evidence is indirect, and further mechanistic studies are required to confirm the therapy's mode-specific contributions. Conclusions Convergent behavioral and neuroscientific evidence has led to the development of the QCore™ tinnitus therapy. There is a need for a rigorous independent evaluation of the platform.